Betting on Secession: Quantifying Political Events Surrounding Slavery and the Civil War - Calomiris, Charles W.; Pritchett, Jonathan (American Economic Review, 2016)
Lincoln's election produced Southern secession, war, and abolition. Using a new dataset on slave sales, we examine connections between news and slave prices for the period 1856–1861. By August 1861, slave prices had declined by roughly one-third from their 1860 peak. That decline was similar for all age and sex cohorts and thus did not reflect expected emancipation without compensation. The decision to secede reflected beliefs that the North would not invade and that emancipation without compensation was unlikely. Both were encouraged by Lincoln's conciliatory tone before the attack on Fort Sumter, and subsequently dashed by Lincoln's willingness to wage all-out war. (JEL D72, D74, D83, G14, H77, N31, N41)